The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s00540-011-1287-0
|View full text |Cite
|
Sign up to set email alerts
|

The impact of hyperlactatemia on postoperative outcome after adult cardiac surgery

Abstract: Hyperlactatemia is common after cardiac surgery. Maximal lactate threshold ≥4.4 mmol/l in the first 10 h after operation accurately predicts postoperative mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 25 publications
(28 reference statements)
5
43
2
2
Order By: Relevance
“…Cardiac surgery patients often develop hyperlactatemia postoperatively [13], which may be affected by several factors, such as the type of surgery, patient body temperature and extracorporeal circulation. Elevated lactate levels in this patient category are also associated with postoperative mortality and a prolonged ICU stay [14,15]. A similar relation was observed for pediatric cardiac surgery patients [16].…”
Section: Introductionmentioning
confidence: 73%
“…Cardiac surgery patients often develop hyperlactatemia postoperatively [13], which may be affected by several factors, such as the type of surgery, patient body temperature and extracorporeal circulation. Elevated lactate levels in this patient category are also associated with postoperative mortality and a prolonged ICU stay [14,15]. A similar relation was observed for pediatric cardiac surgery patients [16].…”
Section: Introductionmentioning
confidence: 73%
“…32,33 In the current trial, enrolled patients had two or more risk factors for hyperlactataemia and the overall incidence of hyperlactataemia was 60% as we expected, which was higher than the results of previous studies (approximately 20%). [2][3][4][5] Patients developing hyperlactataemia showed higher incidences of renal failure and reoperation and longer durations of ventilator care, ICU and hospital stay regardless of the group in the current trial (data not 560 Roh et al shown). These results implicate the value of lactate concentration as a predictor of poor prognosis.…”
Section: Discussionmentioning
confidence: 62%
“…1 It is frequently encountered in cardiac surgery requiring cardiopulmonary bypass (CPB) and has been demonstrated to be associated with adverse outcomes. [2][3][4][5] Risk factors for hyperlactataemia in cardiac surgery include complex surgery, longer duration of CPB, haemodynamic instability, use of vasoconstrictors and hyperglycaemia. [2][3][4] Inherent to the use of CPB, various factors including insufficient pump flow, excessive haemodilution and ischaemia-reperfusion injury are known to contribute to increased myocardial and splanchnic lactate production and compromised hepato-splanchnic lactate extraction.…”
Section: Introductionmentioning
confidence: 99%
“…[86] Consequently, transient hemodynamic improvement may be outweighed by adverse events related to arrhythmias, hyperglycemia, lactic acidosis and beta-adrenergic receptor desentitization. [87,88] A mismatch between increased myocardial oxygen demand and oxygen delivery may further amplify myocardial reperfusion injuries. Increasing levels of catecholamines have also been associated with bacterial growth, increased germ virulence, and biofilm formation.…”
Section: Indications and Risks Of Inotropic Drugsmentioning
confidence: 99%